Flow-mediated dilation and cardiovascular risk prediction: A systematic review with meta-analysis - Ras, Rouyanne T.; Streppel, Martinette T.; Draijer, Richard; Zock, Peter L. (International journal of cardiology, 2013)
Flow-mediated dilation (FMD) is an accepted technique to quantify endothelial function and has shown to have prognostic value for future cardiovascular disease (CVD). The predictive strength of FMD in CVD patients compared to populations not diagnosed for CVD warrants further investigation. We systematically reviewed prospective studies that investigated the association between brachial FMD and future cardiovascular events, with particular focus on the role of underlying health status. To obtain eligible studies, several literature databases were systematically searched through March 2011. Pooled overall risk estimates were calculated separately for continuous risk estimates for CVD (per 1% higher FMD) and for categorical risk estimates for CVD (having high vs. low FMD), based on random-effects models. A total of 23 studies including 14,753 subjects were eligible for inclusion in the meta-analysis. For studies reporting continuous risk estimates, the pooled overall CVD risk was 0.92 (95%CI: 0.88; 0.95) per 1% higher FMD. The observed association seemed stronger (P-value<0.01) in diseased populations than in asymptomatic populations (0.87 (95%CI: 0.83; 0.92) and 0.96 (95%CI: 0.92; 1.00) per 1% higher FMD, respectively). For studies reporting categorical risk estimates, the pooled overall CVD risk for high vs. low FMD was similar in both types of populations, on average 0.49 (95%CI: 0.39; 0.62). Our findings show that brachial FMD is inversely associated with future CVD events, with some indications for a stronger relation in diseased populations. Endothelial dysfunction may be considered relevant for classifying subjects in terms of CVD risk.